Dynamic correspondence of resistance training to sport: A brief review - Suarez, D. G.; Wagle, J. P.; Cunanan, A. J.; Sausaman, R. W.; Stone, M. H. (Strength and Conditioning Journal, 2019)
The proper application of the principle of specificity is essential to any strength and conditioning program. However, the transfer of resistance training to sport is highly complex, difficult to predict, and challenging to assess. This brief review examines the principle of dynamic correspondence as an aid toward better understanding and predicting an exercise or training method's potential transfer to sport. Practical training recommendations are given based on the research reviewed.